A shape memory alloy–based soft morphing actuator capable of pure twisting motion. (June 2015) - Rodrigue, Hugo; Bhandari, Binayak; Han, Min-Woo; Ahn, Sung-Hoon
This article introduces a novel design for a soft morphing actuator capable of pure twisting motion through a pair of shape memory alloy wires embedded in a polydimethylsiloxane matrix at constant and opposite eccentricity across the cross section in opposite directions. This report introduces the design of the actuator, the manufacturing method, and experimental results for the twisting angle and twisting force when varying the dimensions of the matrix of the actuator. Afterward, a simple model is applied to verify the effect of matrix dimensions on the twisting angle of the actuator. The results show that there is an optimal actuator thickness for both the twisting angle and the twisting force of the actuator, that there is a trade-off between the twisting angle and the twisting force for the actuator's thickness, and that a longer length is better for both metrics within the tested dimensions.